Case Report: Infra-Low-Frequency Neurofeedback for PTSD: A Therapist's Perspective - Spreyermann, Regula (Frontiers in Human Neuroscience, 2022)
The practical use of a combination of trauma psychotherapy and neurofeedback [infra-low-frequency (ILF) neurofeedback and alpha-theta training] is described for the treatment of patients diagnosed with complex post-traumatic stress disorder (C-PTSD). The indication for this combined treatment is the persistence of symptoms of a hyper-aroused state, anxiety, and sleep disorders even with adequate trauma-focused psychotherapy and supportive medication, according to the Guidelines of the German Society of Psycho-Traumatology (DeGPT). Another indication for a supplementary treatment with neurofeedback is the persistence of dissociative symptoms. Last but not least, the neurofeedback treatment after a trauma-focused psychotherapy session helps to calm the trauma-related reactions and to process the memories. The process of the combined therapy is described and illustrated using two representative case reports. Overall, a rather satisfying result of this outpatient treatment program can be seen in the qualitative appraisal of 7 years of practical application.